Modern status and dynamics of changes in land resources of the Central Forest-Steppe of Ukraine - Славгородська, Ю. В. (Scientific Progress & Innovations, 2018)
The article considers the current state of use of land resources of the Central Forest-Steppe of Ukraine in the context of administrative regions – Vinnytsa, Kyiv, Kirovograd, Poltava, Cherkasy. Structural distribution of land resources by types of land was analyzed. The Central Forest-Steppe of Ukraine as of 01.01.2016 is 12890,9 thousand hectares. A significant part was occupied by agricultural land – 9321,8 thousand hectares (72,3 %), forests and forest cover areas – 1842,63 thousand hectares (14,3 %), built-up land – 538,4 thousand hectares (4.2 %), water (territories covered with surface water) – 579,5 thousand hectares (4,5 %), other lands – 455,22 thousand hectares. Features of structural distribution were investigated of agricultural land. The excessive level of agricultural development of the territory is determined – 72,3 %, the area’s cultivation is 61,2 %, agricultural land plots – 84,6 %. Such indicators significantly exceed the maximum permissible levels, which indicate extensive use of land. It is established that the structure of land is ecologically unbalanced. The period of 2005–2016 was analyzed a dynamics of land fund changes. Thus, the area of land has undergone some changes, but they are completely unimportant and do not radically change. The reduction of agricultural land is extremely low (0,8 %), the increase in the forest area as an ecolabelling lands is only 0,2 %. The decrease in the share of arable land in the total area of agricultural land is very small – 4,0 thousand hectares (0,03 %). The reduction of arable land was observed in Kyiv region – by 13,7 thousand hectares, in Vinnyts’a – by 4,4 thousand hectares, Cherkasy region – by 1,8 thousand hectares. There is a slight increase in the area of arable land in Kirovograd region – by 1,4 thousand hectares and in Poltava region – by 14,5 thousand hectares. We offered measures to optimize the use of land resources. In particular, an important task in the field of optimization of the structure of the land fund should be measures for the removal of intensive cultivation of degraded, low productive land.